Gender Role and Online News Framing in Sexual Assault Victim Blaming: An Experimental Study - Awalya, Nur; Tetteng, Basti; Kusuma, Perdana (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Abstract. Victim blaming remains prevalent in sexual harassment cases on university campuses and is shaped by media framing and internalised gender roles. This study examined the extent to which gender roles and exposure to framed online news about sexual harassment influence students’ victim-blaming tendencies. Forty psychology undergraduates (aged 18–23 years) from Universitas Negeri Makassar were classified as masculine, feminine, androgynous, or undifferentiated using the Bem Sex Role Inventory. A true experimental design with a randomised pretest–posttest control group was employed. Data were analysed with Two-Way ANOVA and paired-sample t-tests. The analyses revealed no statistically significant main effects of gender role or news framing on victim-blaming scores (p > .05). However, participants exposed to negatively framed news showed a significant posttest increase in victim-blaming (p = .043; d = 0.44). These findings indicate that negative victim-focused framing can heighten the tendency to blame victims. The results highlight the need for media literacy education and gender-awareness programmes to mitigate perceptual bias toward victims. Keywords: Victim Blaming, News Framing, Gender Roles